Dynamic Altered Amplitude of Low-Frequency Fluctuations in Patients With Major Depressive Disorder - Zheng, Ruiping; Chen, Yuan; Jiang, Yu; Wen, Mengmeng; Zhou, Bingqian; Li, Shuying; Wei, Yarui; Yang, Zhengui; Wang, Caihong; Cheng, Jingliang; Zhang, Yong; Han, Shaoqiang (Frontiers in Psychiatry, 2021)
Background: Major depressive disorder (MDD) has been demonstrated abnormalities of static intrinsic brain activity measured by amplitude of low-frequency fluctuation (ALFF). Recent studies regarding the resting state fMRI (rs-fMRI) have found the brain activity is inherently dynamic over time. Little is known, however, regarding the temporal dynamics of local neural activity in MDD. Here, we investigated whether temporal dynamic changes in spontaneous neural activity are influenced by MDD. Methods: We recruited 81 first-episode, drug-naïve MDD patients and 64 age-, gender-, and education-matched healthy controls who underwent resting-state functional magnetic resonance imaging. A sliding window approach was then adopted for the estimation of dynamic ALFF (dALFF), which was used to measure time-varying brain activity and then compared between the two groups. The relationship between altered dALFF variability and clinical variables in MDD patients was also analyzed. Results: MDD patients showed increased temporal variability (dALFF) mainly focused on the bilateral thalamus, the bilateral superior frontal gyrus, the right middle frontal gyrus, the bilateral cerebellum posterior lobe and the vermis. Furthermore, increased dALFF variability values in the right thalamus and right cerebellum posterior lobe were positively correlated with MDD symptom severity. Conclusions: The overall results suggest that altered temporal variability in cortico-cerebellar-thalamic-cortical circuit (CCTCC), involved in emotional, executive and cognitive, are associated with drug-naïve, first-episode MDD patients. Moreover, our study highlights the vital role of abnormal dynamic brain activity in the cerebellar hemisphere associated with CCTCC in MDD patients. These findings may provide novel insights into the pathophysiological mechanisms of MDD.